School Librarians During the Covid-19 - Touku Umar; Nasrullah Nasrullah (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
This study aims to determine the roles and obstacles of school librarians in providing services during the Covid-19. This descriptive study used a qualitative approach. The researchers selected 13 representatives of high schools, vocational high schools, and madrasah aliyah at the same level as public and private. The data were obtained through observations, interviews, and documentation. The study found that school librarians have provided certain library services during the Covid-19 pandemic, namely providing direct services by implementing health protocols, providing digital information sources or e-books, disseminating information via WhatsApp, improving and fixing library infrastructures. Meanwhile, the obstacles faced by school librarians were unpreparedness to face the pandemic, lack of technology facilities and internet access, lack of competency, and minimum library budget.